Effect of consecutive SiCl4 and hydrophobic molecule modification of cotton cloth for fresh oils and used oils removal - Sorapong Janhom (2019)
© 2019 Elsevier Ltd. All rights reserved. The aim of this study was to enhance the hydrophobicity of cotton cloth using silicon tetrachloride (SiCl4) combined with water-repellent agents 1H,1H,2H,2H-perfluorooctyltriethoxysilane (POTS), dimethyldichlorosilane (DMDCS), and stearic acid (SA) for cooking oil and motor oil removal. The cotton cloths were firstly pretreated with SiCl4, at this stage the SiO2 was formed on the cotton cloth surfaces. Secondly, the untreated and SiCl4-treated cotton cloths were separately modified with POTS and DMDCS by chemical vapour deposition and with SA by chemical immersion methods. The surface morphology of the cotton cloths after pretreatment with SiCl4 followed by water-repellent agents was investigated by SEM and EDS techniques. The surface charge of the treated and untreated cotton cloths was also analysed by zeta potential measurement over a pH range of 3-11. The contact angle and the tensile properties of the cotton cloths under various treatment conditions were also investigated, and comparisons were carried out. The results of this study showed that the hydrophobicity of cotton cloth modified by water-repellent agents increased by SiCl4 pretreatment. Untreated and treated cotton cloths were applied to remove used cooking oil and motor oil, and the results were compared with those for the removal of fresh cooking oil and motor oil. The SiCl4 pretreatment prior to bonding with water-repellent agents clearly showed that the POTS-SiCl4 treated cotton cloth performed with the maximum efficiency with regard to oil removal, followed by DMDCS-SiCl4 treated and SA-SiCl4 treated cotton cloths.